Physical and Chemical Characterization of Briquettes Made from a Mixture of Butt Dust and Coconut Shell Charcoal Using Starch Binder - Muhammad Sontang Sihotang; Juwita Febriani Hasibuan; Lilik Waldiansyah (Talenta Publisher, 2025)
The global energy crisis demands the development of alternative energy sources that are environmentally friendly and sustainable. One potential solution is the utilization of industrial waste and biomass into solid fuel in the form of briquettes. This study aims to evaluate the characteristics of briquettes made from industrial waste of PT. INALUM, namely butt dust, combined with coconut shell charcoal using starch as a binder. Five variations of butt dust and coconut shell charcoal compositions were tested, namely 100:0%, 80:20%, 60:40%, 40:60%, and 20:80%. Each variation was analyzed for ash content, moisture content, volatile matter, fixed carbon, density, and calorific value. The results showed that the raw material composition influenced the physical and chemical properties of the briquettes. Briquettes with a 100:0% ratio produced the best performance, with the highest calorific value of 9431.14 cal/g, density of 0.2324 g/cm³, ash content of 2.09%, moisture content of 4.22%, volatile matter of 11.0%, and fixed carbon of 82.7%. The addition of coconut shell charcoal tended to reduce calorific value and increase ash content. These findings confirm that butt dust has great potential as the main raw material for producing high-quality briquettes. Practically, the results support the utilization of industrial waste as an alternative energy source, contributing to national energy security while reducing environmental impacts.